2013
DOI: 10.1109/lsp.2013.2261494
|View full text |Cite
|
Sign up to set email alerts
|

Exact Fast Computation of Optimal Filter in Gaussian Switching Linear Systems

Abstract: This paper presents a contextual algorithm for the approximation of Baum's forward and backward probabilities, which are extensively used in the framework of Hidden Markov chain models for parameter estimation. The method differs from the original algorithm by taking into account only a neighborhood of limited length and not all the data in the chain for computations. It then becomes possible to propose a bootstrap subsampling strategy for the computation of forward and backward probabilities, which greatly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The CGOMSM family of models is very flexible, so that it was possible to build a model as a close approximation to the CGPMSM (also see theoretical justifications in [17] of its closeness with the classical CGLSSM). We showed that, at least in the context of this study, our filter showed comparable efficiency with respect to a suited particle filter, while being much faster.…”
Section: Discussionmentioning
confidence: 99%
“…The CGOMSM family of models is very flexible, so that it was possible to build a model as a close approximation to the CGPMSM (also see theoretical justifications in [17] of its closeness with the classical CGLSSM). We showed that, at least in the context of this study, our filter showed comparable efficiency with respect to a suited particle filter, while being much faster.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, any stationary CGLSSM is given by p(r 2 1 ), p(x 2 1 |r 2 1 ) and p(y 1 |r 1 ). If these distributions are the only information about some physical system, then a Model 2 can capture them as well [23]. Specifically, p(r 2 1 ), p(x 2 1 |r 2 1 ) and p(y 2 1 |r 2 1 ) would be the same in CGLSSM and Model 2, and only p(x 2 , y 1 |r 2 1 ) would differ.…”
Section: Stationnary Conditionnaly Gaussian Observed Markov Switchingmentioning
confidence: 99%
“…Let us remember that SCGOMSMs can be very close to the classic "conditionally Gaussian linear state-space model" (CGLSSM) [11,12], which does not offer the possibility of fast smoothing [5].…”
Section: Stationary Conditionally Gaussian Observed Markov Switching mentioning
confidence: 99%